Climate Change And The Challenges Of Setting Countries' Maritime Boundaries In The Perspective Of International Law - Ashri Rose Dhuhaningrum; Wijayono Hadi Sukrisno; Adystia Sunggara (PT. Hafasy Dwi Nawasena, 2026)
Climate change is a global phenomenon that has various impacts on human life, including the maritime territories of states. Rising sea levels, coastal erosion, and the submergence of small islands have the potential to alter geographical conditions that have long served as the basis for the determination of maritime boundaries. These changes give rise to legal issues related to territorial certainty, the exercise of state sovereignty, and the management of marine resources. This study aims to analyze the regulation of maritime boundaries under international law and to examine the challenges posed by climate change to the determination of state maritime boundaries. The research addresses two main questions: how maritime boundaries are regulated under international law and what challenges arise in determining maritime boundaries due to climate change. The study employs normative legal research using statutory and conceptual approaches through an examination of various international legal instruments, particularly the United Nations Convention on the Law of the Sea (UNCLOS) 1982. The findings indicate that climate change has the potential to affect baselines, which serve as the basis for measuring a state's maritime zones. Furthermore, issues of vague norms, conflicts of norms, and legal vacuums exist within international law concerning the status of maritime boundaries affected by geographical changes resulting from sea-level rise. This study concludes that the development of a more adaptive international legal framework is necessary to ensure legal certainty, protect state sovereignty, and prevent future maritime disputes.